GUARANTEEING THE RIGHT TO VOTE FOR INDIVIDUALS WHO MARRY UNDERAGE IN THE PERSPECTIVE OF THE CONSTITUTION : Lex Principle Approach Specialist Derogat Legi Genrali and Homo Sacer Theory Giorgio Agamben - Putrawan, Agus Dedi; Andrean, Muhammad; Tabibuddin, Ahmad Saleh; Fauzi, Fauzi (Politea : Jurnal Politik Islam, 2025)
This study aims to analyze the guarantee of the right to vote for individuals who marry underage from a constitutional perspective with the principle of lex specialis derogat legi generali approach. Normative conflicts occur between the Election Law, the Child Protection Law, the Marriage Law, and the Civil Registration Law. Based on this principle, special laws (lex specialis) can override general laws (lex generalis). Thus, married minors should be able to exercise their right to vote because the Election Law is special in the implementation of elections. This study uses the homo sacer theory of Giorgio Agamben. In this theory, individuals under the age of 17 who marry are considered "human beings without protection" because they do not acquire constitutional rights. They are abandoned by the state even though they are still recognized as part of the state. Agamben called Homo Sacer a group that lost its political rights but remained an object of power without legal protection. This study uses a qualitative method, collecting primary data through interviews and secondary data from documentation. Data analysis was carried out with an interactive model: collection, reduction, presentation of data, and drawing conclusions. The results of the study show that individuals who marry underage do not get the right to vote because the state fails to resolve the conflict of norms. This condition causes them to slip into the "identity vacuum" as homo sacer, abandoned due to the state's inability to maintain sovereignty and protect the constitutional rights of its citizens.